Bancários e oligopolização: avanços e limites nas lutas contra a superexploração do trabalho na ditadura no Brasil (1964-1980) - Rocha, Danielle Franco da (2013)
This paper investigates the bank workers struggles against the overexploitation of labor during the dictatorship in Brazil, especially between the years of 1964 to 1980. Throughout our research we looked into their purposes, their instruments, their strategies, and their most important struggles against post-64 dictatorship. We begin studying the struggles of bank workers in this period, because we recognize the importance of their resistance and confrontation against the deepening of the process of oligopoly of capital. The Brazilian economy was going through an overwhelming concentration and centralization of capital, which gained oligopolistic characteristics, therefore it s critical to understand that moment of intense labor struggles in Brazil, and of the workers strategies against the deepening of the Brazilian subordination to monopolistic capitalism